Low uptake of cervical cancer screening among HIV positive women in Gondar University referral hospital, Northwest Ethiopia: cross-sectional study design - Abebe Dires Nega; Mulat Adefris Woldetsadik; Abebaw Addis Gelagay (BMC, 2018)
Abstract Background Cervical cancer is one of the leading causes of death in women worldwide. Majority of the cases are found in developing countries. The increasing risk of cervical cancer death and the high prevalence of human papilloma virus (HPV) infection in Human immuno-deficiency virus(HIV) positive women calls for determining the level of premalignant cervical cancer (Ca) screening uptake. So, this study aimed to assess the uptake of cervical cancer screening and its associated factors. Methods An institution based cross sectional study was conducted from April to May, 2016, among adult HIV positive women attending care and treatment at Gondar University Referral Hospital. The data were collected using an interviewer administered questionnaire. Bivariate and multivariable logistic regression analyses were used to determine the presence and the degree of association between dependent and independent variables. In the multivariable logistic analysis, a P-value of < 0.05 and odds ratio with a 95% confidence interval were considered to determine independent predictors for the uptake of cervical cancer(Ca) screening. Results The life-time uptake of cervical cancer screening among HIV positive women was 10% (95% Confidence Interval(CI): 7.3-12.8). In multivariable the analysis, women with primary education (Adjusted Odds Ratio(AOR) = 3.92, 95%CI:1.70-8.99), secondary education (AOR = 3.84, 95%CI: 1.50-9.83), and tertiary level education (AOR = 4.16, 95%CI: 1.24-13.98), having a child (AOR = 3.02, 95%CI: 1.23-7.46), diagnosed as HIV positive ten years back or more (AOR = 2.71, 95% CI: 1.06-6.97), and Cell Differentiation 4(CD4) count of less than or equal to 200cell/mm3 (AOR = 5.29, 95% CI: 2.58-10.83) were significantly associated with the uptake of cervical cancer screening. Conclusion In this study, the uptake of cervical cancer screening was very low. Educational status, parity, length of time after diagnosis as HIV positive, and CD4 count are important predictors of cervical cancer screening. Health care workers and cervical cancer prevention and control program coordinators and implementers need to provide counseling services for all Anti-retroviral Therapy(ART) care attendants. So as to explore the root causes for the low utilization of precancerous stage of cervical Ca screening service, conducting a study on the supply side with a qualitative component is mandatory.